Eksplorasi Gaya Bahasa Majāz Mursal sebagai Strategi Retorika dalam Dakwah Digital Berbahasa Arab - Rahmayanti, Sri; Haniah, Haniah; Harjum, Mohamad; Fadillah Amin, Nur; Hamzah, Nur; Husnul Khatimah, A. (Institut Agama Islam Negeri Metro, 2025)
In the digital era, social media has become a strategic medium for disseminating Islamic da’wah with broad and transboundary reach. This condition requires the application of effective rhetorical strategies, one of which is the use of majāz mursal. This study aims to identify the forms of majāz mursal found in Arabic digital da’wah discourse and to explain their contribution to the effectiveness of da’wah communication. This research employs a descriptive qualitative approach with a discourse analysis and Arabic rhetorical (balāghah) framework. The research data consist of five Arabic digital da’wah contents purposively selected from TikTok and Instagram platforms, including short motivational videos, kalām ḥikmah (words of wisdom), and da’wah captions. Data were collected through content documentation and semi-structured interviews with ten informants. Data analysis was conducted through several stages, namely identifying majāz expressions, classifying the types of majāz mursal based on semantic relationships, and interpreting their rhetorical functions within the context of digital da’wah. The findings indicate that majāz mursal with sababiyyah, musabbabiyyah, kulliyyah, and juz’iyyah relationships are dominantly employed to clarify moral messages, enhance linguistic aesthetics, and strengthen the persuasive power of da’wah. Therefore, the use of majāz mursal can be considered an applicative and effective rhetorical strategy in digital da’wah practices.